Architecture and Fine Arts in the Shaybanid Period - Toshmurodova Sarvinoz Quvondiq qizi; Ergashev Ahmad Abdug' afforovich; Bengmatov Alibek Qahramon o'g'li (International Journal on Orange Technologies, 2021)
This article briefly describes the contribution of the Shaybani dynasty to the development of culture in the 16th century, the architectural samples built during this period, and the development of miniature art.